Shock response and prediction model of equation of state for aluminum powder/rubber matrix composites - Jun-bao Li (Materials & Design, 2020)
The shock response of aluminum powder/rubber matrix composites containing 40, 50, and 60 vol% Al was investigated using the plate impact test and explosive loading technique. The shock stress in the range of 0.61–13.97 GPa was measured and the free surface velocity of the specimen was monitored using the displacement interferometer system for any reflector. The composites' shock Hugoniots were obtained in terms of shock velocity, particle velocity, and shock stress, and a theoretical model for predicting the Hugoniots of the composites was proposed. The results revealed that a steady shock front was generated and propagated in the composites. The shock stress was attenuated with the propagation distance and the attenuation effect became more obvious as the stress increased. The shock velocity had a linear relationship with the particle velocity and the relationships for the composites with 40 and 50 vol% Al were very similar. By comparing the Hugoniots of the three materials and rubber, it was found that the shock behavior of the composites was similar to that of the matrix rubber. Additionally, the rubbery type shock response changed as the aluminum content increased. The shock behavior of the composites was adequately described by the proposed theoretical model.